Pengaruh Diamond Theory Terhadap Fraudulent Financial Statements Dengan Komisaris Independen Sebagai Variabel Pemoderasi - Oktavianasari, Ira; Prajanto, Agung; Dapit Pamungkas, Imang; Wikan Kinasih, Hayu (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2024)
This research uses a fraud diamond model analysis which consists of four factors, namely pressure, opportunity, rationalization, and cability, aiming to test and analyze the influence of pressure, opportunity, rationalization, cability on Fraudulent Financial Statements with the Independent Commissioner as a moderating variable. The sample for this research was selected using purposive sampling, namely BUMN companies for the 2019-2022 period that met the criteria. Using a quantitative analysis approach, regression was used as an analysis method and a total of 96 samples were included in this research. Statistical data analysis to test the hypothesis was carried out with the help of WarpPLS software version 8.0. This research shows that pressure, opportunity and ability have a positive effect on Fraudulent Financial Statements, while rationalization has a negative effect on Fraudulent Financial Statements. Apart from that, the Independent Commissioner only moderates the relationship between capability and Fraudulent Financial Statements.